Oral Neutrophils: Underestimated Players in Oral Cancer - Domnich, Maksim; Riedesel, Jana; Pylaeva, Ekaterina; Kürten, Cornelius H. L.; Buer, Jan; Lang, Stephan; Jablonska, Jadwiga (Frontiers in Immunology, 2020)
The composition of the oral milieu reflects oral health. Saliva provides an environment for multiple microorganisms, and contains soluble factors and immune cells. Neutrophils, which rapidly react on the changes in the microenvironment, are a major immune cell population in saliva and thus may serve as a biomarker for oral pathologies. This review focuses on salivary neutrophils in the oral cavity, their phenotype changes in physiological and pathological conditions, as well as on factors regulating oral neutrophil amount, activation and functionality, with special emphasis on oral cancer and its risk factors.